The invisible raptor [videorecording (Blu-Ray)] - Capes, Mike; Wickham, Johnny; Capes, Mike; Shackelford, David; Stamos, Caitlin McHugh; Martin, Sandy; Astin, Sean (Well Go USA Entertainment, 2025)
After a top-secret experiment goes wrong, a hyper-intelligent invisible raptor escapes the lab and begins wreaking havoc in the surrounding neighborhood. When the creature's identity is uncovered, it soon becomes clear that a disgraced paleontologist alongside his ex-girlfriend, an unhinged amusement park security guard, and a local celebrity chicken farmer is the town's only hope for surviving the raptor's ravenous rampage.